Data on liquid gated CNT network FETs on flexible substrates - Thanihaichelvan, M.; Browning, L.A.; Dierkes, M.P.; Reyes, R.M.; Kralicek, A.V.; Carrahe, C.; Marlow, C.A.; Plank, N.O.V. (University of Jaffna, 2018)
This article presents the raw and analyzed data from a set of experiments performed to study the role of junctions on the electrostatic gating of carbon nanotube (CNT) network field effect transistor (FET) aptasensors. It consists of the raw data used for the calculation of junction and bundle densities and describes the calculation of metallic content of the bundles. In addition, the data set consists of the electrical measurement data in a liquid gated environment for 119 different devices with four different CNT densities and summarizes their electrical properties. The data presented in this article are related to research article titled “Metallic-semiconducting junctions create sensing hot-spots in car bon nanotube FET aptasensors near percolation” (doi:10.1016/j.bios. 2018.09.021) [1]